An investigation of the frequency dynamics of spillovers and connectedness among GCC sectoral indices - Kapar B; Billah SM; Rana F; Balli F (Elsevier Inc, 2024)
We examine intra-regional patterns of return and volatility spillovers between economic sectors of GCC over the period from 2007 to 2021 at different frequencies. First, we investigate the connectedness of sectoral equity returns and volatilities by applying TVP-VAR frequency connectedness method and explore the different patterns and magnitudes. Second, we explore possible determinants of sectoral equity return and volatility spillovers. We identify that spillovers are regime dependent increasing their intensity during turmoil periods such as 2007–2008 crisis, 2014 oil price crash and 2020 COVID-19 pandemic. The level of contagion is the highest in the financial sector and the lowest in the energy sector. In general, while Bahrain stock market is segmented from other markets in many sectors, Saudi Arabia is losing its dominance position to UAE and Qatar to transmit shocks to other countries. In line with the literature, the liquidity and profitability positions significantly affect the extent of the spillovers which are highly dispersed across sectors. Particularly, the sectors that have high leverage tend to transmit the shock rather than absorb. Our findings confirm the heterogeneity of sectoral spillover returns and volatilities, thereby suggesting that portfolio managers can monitor the magnitude of the spillovers by controlling the financial performance of the firms and guide their investment decisions accordingly at different time horizon.
Keywords: GCC stock markets; Sectoral equity spillovers; Frequency connectedness; Determinants of spillovers